Complex precursory activity prior to the c.7600 yr BP Mazama (Crater Lake, USA) eruption - Buckland, Hannah; Cashman, Katharine; Rawlings, Jessica; Day, Lilli; Young, Simon (Volcanica, 2024)
Large magnitude explosive volcanic eruptions occur globally at a rate of 1–2 per 1000 years and can cause devastating global impacts. Despite the risk these eruptions pose, we have no reliable method to forecast whether lower magnitude eruptions are precursory to a larger event. Here we ask whether we can identify unique precursors to a large eruption using data from the runup to the ~7.6 ka eruption of Mount Mazama (Crater Lake, Oregon). We present new compositional and textural data that suggest the precursory sequence involved at least three distinct eruptions. In this way, the climactic Mazama eruptive sequence resembles the four-month build-up to the 1883 Krakatau eruption. We highlight the distinct properties of the lowermost unit that suggests at least one precursory eruption tapped a distinct magma reservoir supporting the idea that to evacuate large magma volumes you require the pre- or syn-eruptive amalgamation of multiple melt lenses.